Antihyperglycemic, Antidiabetic, and Antioxidant Effects of Garcinia pedunculata in Rats - Ali, Md. Yousuf; Paul, Sudip; Tanvir, E. M.; Hossen, Md. Sakib; Rumpa, Nur-E Noushin; Saha, Moumoni; Bhoumik, Nikhil Chandra; Islam, Md. Aminul; Hossain, Md. Sabir; Alam, Nadia; Hua Gan, Siew; Khalil, Md. Ibrahim (Hindawi Publishing Corporation, 2017)
The antihyperglycemic, antidiabetic, and antioxidant potentials of the methanolic extract of Garcinia pedunculata (GP) fruit in rats were investigated.The acute antihyperglycemic effect of different doses of GP was studied in normalmaleWistar rats. Diabetes was induced by streptozotocin (STZ) injection in another cohort of maleWistar rats and they showed significantly higher blood glucose and glycated hemoglobin (HbA1c) levels, altered lipid profiles, and lower insulin levels compared to nondiabetic control animals. There were increased lipid peroxidation and reduced levels of cellular antioxidant enzymes in different tissues of diabetic rats. However, oral administration of GP extracts, especially the highest dose (1000mg/kg), significantly ameliorated hyperglycemia (42%); elevated insulin levels (165%); decreased HbA1c (29.4%); restored lipid levels (reduction in TG by 25%, TC by 15%, and LDL-C by 75% and increase in HDL-C by 4%), liver and renal function markers, and lipid peroxidation (reduction by 52% in the liver, 39% in the kidney, 44% in the heart, and 46% in the pancreas); and stimulated tissue antioxidant enzymes to near normalcy. Overall, the findings suggest that GP fruit is effective against hyperglycemia and could be used in the treatment of diabetes and its complications and other oxidative stress-mediated pathological conditions.